Factors Influencing Consumer Decisions Towards The Purchase Of Straw Mushrooms In Banda Aceh City - wani, cut eva; Wiriani, Erni (Indonesian Journal Economic Review (IJER), 2024)
This research is descriptive in nature, namely to explain the problems that arise especially in the world of Straw Mushroom Cultivation Business in Banda Aceh City and its Marketing process. The purpose of this study is to determine how much influence Consumer Decisions have on Straw Mushroom Purchases in Banda Aceh City. The scope of this study is the field of marketing science that focuses on the marketing mix on consumer behavior in choosing to buy Straw Mushrooms, the location of the study is in Banda Aceh City. The number of research samples was 100 people taken by Purposive Sampling. The results of the F Test (overall) show that the product factors (x1), price (x2), distribution (x3), Promotion (x4), together have a significant effect on the decision to purchase Straw Mushrooms in Banda Aceh City, this can be seen from the F count of 0.166 and F table 0.288. This means that statistically it proves that the alternative hypothesis (Ha) proposed can be accepted and rejects the null hypothesis (Ho). Meanwhile, partially, the price variable does not have a significant effect on the decision to purchase Straw Mushrooms in Banda Aceh City, while the product, distribution and promotion variables have a significant effect on influencing the decision to purchase Straw Mushrooms in Banda Aceh City.